2015
DOI: 10.4238/2015.november.18.38
|View full text |Cite
|
Sign up to set email alerts
|

VKORC1 rs2359612 and rs9923231 polymorphisms correlate with high risks of cardiovascular and cerebrovascular diseases

Abstract: ABSTRACT. We aimed to confirm the correlations between rs2359612 and rs9923231 single nucleotide polymorphisms (SNPs) in the vitamin K epoxide reductase complex subunit 1 (VKORC1) gene and the risk of cardiovascular and cerebrovascular diseases (CCVDs) using metaanalysis. Electronic databases were exhaustively searched for relevant case-control studies by employing stringent inclusion and exclusion criteria. Manual retrieval was also conducted to obtain additional pertinent literature. The STATA statistical so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recently, a meta-analysis conducted by Li et al [ 26 ] demonstrated that G-1639A and T2255C SNPs in VKORC1 gene might contribute to the risk of cerebrovascular and cardiovascular diseases. Herewith, the above data showed that minor alleles in some populations can be the wild alleles in other populations, which leads to different interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis conducted by Li et al [ 26 ] demonstrated that G-1639A and T2255C SNPs in VKORC1 gene might contribute to the risk of cerebrovascular and cardiovascular diseases. Herewith, the above data showed that minor alleles in some populations can be the wild alleles in other populations, which leads to different interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic predisposing factor is an important component in the mechanism of CTEPH patients. Li et al (2014) in a meta-analyse of 10 clinical case-control studies (7329 patients with cardiovascular disease and 7951 healthy controls) demonstrated that VKORC1 rs2359612 and rs9923231 polymorphisms correlate with high risks of cardiovascular and cerebrovascular diseases [15].…”
Section: Discussionmentioning
confidence: 99%